Voting Gap by Origin - Momi Dahan (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study examines the voting patterns of Mizrahi and Ashkenazi in ten general elections held since the early 2000s in rural and urban areas in Israel, utilizing a new classification method of origin of immigrants and their descendants based on surnames alongside the traditional classification by continent of birth. The study reveals relatively sharp fluctuations across elections in the size of origin gap in voting for right-wing party bloc between Mizrahi and Ashkenazi. According to the empirical analysis, the origin voting gap in the general elections held in 2022 was five times the gap found in the elections held in 2006, and more than twice that of the elections held in 2009. Sharp fluctuations in the voting gap undermine the protest vote hypothesis that discrimination against immigrants of Mizrahi origin in the past is the main factor behind their current political behavior. In all ten elections examined, the gap in voting for the right-wing party bloc between Mizrahi and Ashkenazi voters disappears or decreases considerably when differences in the level of education and degree of religiosity are neutralized. This study also reveals an interesting trend in the political behavior of voters with high education level. They are more likely to vote for the center-left bloc in recent elections, in contrast to their similar support for both blocs recorded in previous elections.
Keywords: 330